AYAT-AYAT HUJAN DALAM PERSPEKTIF WAHBAH AZ-ZUHAILI - Utami, Charissa Myla; Hanum, Sarmidah; AM, Supriadi (JIQTA: Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
Rain is a natural phenomenon that occurs when sea air evaporates and forms clouds in water droplets, then these water droplets fall to the earth. Many people believe that rain can damage the environment around residents, when in fact environmental damage occurs due to human actions. The focus of this research is the Islamic perspective on the meaning of rain in human life in the book of tafsir al-munir by Wahbah az-Zuhaili. By using a thematic study of the meaning of rain. The aim of this research is to avoid misunderstandings about the fall of rain. The results of this research show that rain is a gift from Allah SWT which provides benefits to all living creatures on earth, it can grow plants that produce fruit that can be enjoyed by living creatures on earth and also brings life to barren or dead land. This research only focuses on several letters, namely surah al-Baqarah verse 22, surah al-An'am verse 99, and Fussilat verse 39.